(3GdMGTjI GdeajOI Ydi TQM JdNjU GdeaJGMs - (3dWa Gddg , dWa Gddg Hf eMeO GdZjGK GdXajQj, bWH GdOjf,J (B1035 (3g` s
(3ChdgG (B:s
(3bhdg HGddSGf bHd hbO jfWHb Ydi GdEJjGf s
(3BNQgG (B:s
(3GdPi NJe Hg ShQI GdHbQI hGdhUGjG s
(3GdfSNI HgG MhGTs
(3hQO GdYfhGf GdCUdi ai cTa GdXfhf (B2/ 1764s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdHdGZIs